Rare form of mite dermatitis - Tatyana A. Belousova; Mariya V. Kail-Goryachkina (LLC "MEDIAFORMAT", 2021)
Acariasis is a group of common disorders caused by mite infestation of the skin. Trombiculosis (thrombidiasis) is one of the rare seasonal (summer) types of dermatitis, caused by the ectoparasitized larvae (chiggers) of harvest mites in the skin. During the past decade, physicians and biologists in many countries reported the Trombiculidae mites population growth and the increased prevalence of seasonal dermatitis due to these mites. The number of severe trombiculosis cases has increased in Europe, especially in Western Germany and Great Britain. The data on epidemiology, clinical features, diagnosis, treatment and prevention of trombiculosis are provided. The case study is reported.